Історико-філософський аспект природно-правового і позитивно-правового принципів праворозуміння - Васецький, В.Ю. (Альманах права, 2012)
Розглядаються питання історичного розвитку філософських концепцій праворозуміння. Основна увага приділяється розвитку природно-правового і позитивно-правового напрямків. Відзначається поширення філософського розуміння права, що пов’язується з такими цінностями, як свобода, рівність, справедливість, права та свободи людини. Рассматриваются вопросы исторического развития философских концепций правопонимания. Основное внимание уделяется развитию естественно-правового и позитивно-правового направлений. Отмечается распространение философского понимания права, которое связывается с такими ценностями, как свобода, равенство, справедливость, права и свободы человека. The article is dedicated to the issues of historical development of philosophical concepts of legal doctrines. The main attention is given to the development of natural right and positive law doctrines. The historical evaluation of natural right doctrine comes from the Ancient Greece and Ancient Rome, Medieval Europe, New Time, Classical German Philosophy from the end XVIII up to the beginning of ХІХ century. The basic features of historical development of positive law doctrines are noted. The article try to show the pros and contras of natural right and positive law doctrines. It was given the general ideas of the doctrines in legal philosophy. It is indicated that one of modern Ukrainian general theoretical jurisprudence directions is fundamental methodology. The basic direction of Ukrainian legal science defines the following processes: globalization, nonformalization, anthropology. It is specified in studying the origins, functioning and development of human rights. It is described the distribution of philosophical understanding of law in connection to the values like freedom, equality, justice, human rights. Pursuant to the conclusion nowadays the philosophical valuable factors strengthen leading legal principles that has not only theoretical, but also practical value for modern Ukraine.